2021
DOI: 10.48550/arxiv.2110.03101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SPEED+: Next-Generation Dataset for Spacecraft Pose Estimation across Domain Gap

Tae Ha Park,
Marcus Märtens,
Gurvan Lecuyer
et al.

Abstract: Autonomous vision-based spaceborne navigation is an enabling technology for future on-orbit servicing and space logistics missions. While computer vision in general has benefited from Machine Learning (ML), training and validating spaceborne ML models are extremely challenging due to the impracticality of acquiring a large-scale labeled dataset of images of the intended target in the space environment. Existing datasets, such as Spacecraft PosE Estimation Dataset (SPEED), have so far mostly relied on synthetic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The dataset labels include quaternion and 3D depth distance. In 2021, they further proposed Next-Generation Dataset for Spacecraft Pose Estimation across Domain Gap, called SPEED+ [35]. In addition to the 60,000 synthetic images used for training, SPEED+ includes 9,531 real images taken from Tron.…”
Section: A Space Target Datasetsmentioning
confidence: 99%
“…The dataset labels include quaternion and 3D depth distance. In 2021, they further proposed Next-Generation Dataset for Spacecraft Pose Estimation across Domain Gap, called SPEED+ [35]. In addition to the 60,000 synthetic images used for training, SPEED+ includes 9,531 real images taken from Tron.…”
Section: A Space Target Datasetsmentioning
confidence: 99%
“…In particular, the Cygnus dataset [4] contains 540 pictures of the Cygnus spacecraft in orbit in conjunction with 20k synthetic images generated with Blender [1]. However, the main limitation of spaceborne images is SPARK [20] SPEED [15] SPEED+ [21] URSO [26] SwissCube [13] Cygnus [4] Prisma12K [22] Prisma25 [7] the lack of accurate pose labels and their limited diversity in terms of pose distribution. To overcome these difficulties, laboratory setups trying to mimic space conditions currently represent the de facto target domain for spacecraft pose estimation algorithms [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main limitation of spaceborne images is SPARK [20] SPEED [15] SPEED+ [21] URSO [26] SwissCube [13] Cygnus [4] Prisma12K [22] Prisma25 [7] the lack of accurate pose labels and their limited diversity in terms of pose distribution. To overcome these difficulties, laboratory setups trying to mimic space conditions currently represent the de facto target domain for spacecraft pose estimation algorithms [21]. Moreover, laboratories offer monitoring mockup poses and environmental conditions to ensure a higher quality of the data [30,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related studies presented in [ 34 , 35 , 36 ] showed that CNNs can simplify the feature detection and matching process while increasing estimation accuracy. Furthermore, when using CNNs for pose estimation, reducing the domain gap between space imageries and synthetically generated images is another critical topic to be considered [ 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%